The discourse argumentative markers: comparative study between the Arabic and the Spanish - El Messaoudi Rifi, Ismail (Anaquel de Estudios Árabes, 2018)
This research aims to contribute to the comparative study of Arabic and Spanish discourse markers, which are one of the mechanisms of cohesion that contribute to the creation of internal coherence inside the text. It is a descriptive and explanatory study, through which- from the linguistic-discursive and contrastive points of view- we propose to detect the points of convergence and divergence between the two systems of discourse argumentative markers (the connectors) of written language in Spanish and Arabic. The general procedure of the discursive and contrastive analysis adopted is to classify the discourse markers of our study into categories, to identify the units that make up each category and their discursive functions in Arabic and Spanish, and finally to perform a contrastive comparison by categories in the corpus of the chosen Translation. After presenting the virtual characteristics of the connectors in the language, we study how they are updated in the original text and how they are retrieved in the target text. From the textual perspective, this discursive phenomenon is analyzed taking into account the context of its appearance at the textual level.